Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans - Blake, James A. (Zootaxa, 2016)
A new name, Kirkegaardia, is proposed to replace Monticellina Laubier, 1961, a bitentaculate cirratulid polychaete genus, that is a junior homonym of the turbellarian Monticellina Westblad, 1953 (Platyhelminthes, Rhabdocoela). In addition, the opportunity is taken to complete a major revision of the genus including the redescription, revalidation, and separation of three species previously referred to synonymy with K. dorsobranchialis (Kirkegaard, 1959) and five other previously described species. In addition, 16 new species are described from the western North Atlantic, eastern and central Pacific, off western South America, and seas around Antarctica, bringing the total number of species in the genus to 38. Included are two new species of the unusual mud ball worms, first reported as Tharyx luticastellus Jumars, 1975, from southern California deep basins. A review of all 38 species reveals that three distinct species groups may be identified within the genus in addition to 5–6 species that may eventually be referred elsewhere. This review includes a discussion of the taxonomic characters and various newly defined character states that are found among species of Kirkegaardia. Several of these are unique among the Cirratulidae.